THE CAMPAIGN OF WEARING MASK AND WASHING HANDS WITH HAND SANITIZER AMONG STREET VENDORS KAYURINGIN JAYA BEKASI SELATAN - Hilda Meriyandah Agil; Lisna Agustina (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
The high number of COVID-19 cases in Bekasi requires interventions that focus on communities with high exposure of virus, one of which was street vendors. With the aim of improving the knowledge and awareness of street vendors to implement health protocols, this campaign was carried out. A total of 50 street vendors participated in this activities and were evaluated to have increased knowledge, especially in the behavior of washing hands with hand sanitizers and the importance of wearing masks in public places.